2022
DOI: 10.1088/2053-1583/ac4e9d
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic origin of multiferroic order in monolayer NiI2

Abstract: The discovery of multiferroic behavior in monolayer NiI2 provides a new symmetry-broken state in van der Waals monolayers, featuring the simultaneous emergence of helimagnetic order and ferroelectric order at a critical temperature of T=21 K. However, the microscopic origin of multiferroic order in NiI2 monolayer has not been established, and in particular, the role of non-collinear magnetism and spin-orbit coupling in this compound remains an open problem. Here we reveal the origin of the two-dimensional mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…The potential type II multiferroicity of monolayer and few-layer NiI 2 could be derived from the electric polarization induced by spin helical order. 26 In addition, multiferroics can also be achieved by designing extrinsic FM−FE multiferroic van der Waals (vdW) heterostructures by integrating these two Over the past five years, researchers have made a significant breakthrough in achieving 2D magnetic ultrathin films from non-vdW materials, 29,30 which overcomes the limitation of both mechanical exfoliation and layered crystals of bulk counterparts. 31−40 To date, 2D non-vdW crystals of CrSe, 31 CrTe, 32 CrTe 2 , 33 Cr 2 Te 3 , 34 MnTe, 35 FeSe, 36 α-MnSe 2 , 37 Fe 7 Se 8 , 38 and VO 2 39 have been successfully synthesized, exhibiting a high Curie or Neél temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential type II multiferroicity of monolayer and few-layer NiI 2 could be derived from the electric polarization induced by spin helical order. 26 In addition, multiferroics can also be achieved by designing extrinsic FM−FE multiferroic van der Waals (vdW) heterostructures by integrating these two Over the past five years, researchers have made a significant breakthrough in achieving 2D magnetic ultrathin films from non-vdW materials, 29,30 which overcomes the limitation of both mechanical exfoliation and layered crystals of bulk counterparts. 31−40 To date, 2D non-vdW crystals of CrSe, 31 CrTe, 32 CrTe 2 , 33 Cr 2 Te 3 , 34 MnTe, 35 FeSe, 36 α-MnSe 2 , 37 Fe 7 Se 8 , 38 and VO 2 39 have been successfully synthesized, exhibiting a high Curie or Neél temperature.…”
mentioning
confidence: 99%
“…Notably, Song et al and Ju et al have recently found experimental evidence of intrinsic multiferroicity in monolayer and bilayer NiI 2 . The potential type II multiferroicity of monolayer and few-layer NiI 2 could be derived from the electric polarization induced by spin helical order . In addition, multiferroics can also be achieved by designing extrinsic FM–FE multiferroic van der Waals (vdW) heterostructures by integrating these two kinds of components together.…”
mentioning
confidence: 99%
“…For the particular case of electric and magnetic orders, a magnetoelectric coupling [34] provides a venue for the electric control of magnetic orders, a feature with a huge potential interest. Different multiferroic mechanisms have been studied over the past years, both in bulk compounds [35][36][37] and recently in two-dimensional monolayers [38][39][40]. In the realm of moiré materials, the strongly correlated states emerging in twisted systems provide an additional platform to artificially engineer multiferroics associated with the moiré length scale.…”
Section: Introductionmentioning
confidence: 99%
“…For example, type-II multiferroicity was reported in bulk NiBr 2 22 , NiI 2 23 and MnI 2 24,25 , where the onset of helimagnetic phases breaks inversion symmetry leading to spin-induced ferroelectricity. Such a multiferroic phase has been recently reported to survive down to the monolayer limit of NiI 2 26,27 , while monolayer NiBr 2 and NiCl 2 have been proposed as half-excitonic insulators 28 . The electronic structure of the 3d M X 2 compounds has been recently analyzed 29,30 ; however the magnetic exchange couplings and SOC-driven anisotropic contributions have not been fully addressed and require deeper investigation.…”
Section: Introductionmentioning
confidence: 99%